State policies that promote, and that inhibit, improved public health: An exploratory analysis of paid sick leave - Wolf, Douglas A. (Frontiers in Public Health, 2022)
The United States has no national requirement that employers provide paid sick leave (PSL) to their employees, despite the many established public health benefits of PSL access. Many states, and some localities, have passed laws requiring PSL within their jurisdictions. Past studies have shown that these PSL mandates are effective in promoting increased PSL access. However, past studies have not considered two other commonly-used state policy initiatives—PSL preemption and right-to-work laws—that could hypothetically influence employers’ decisions to provide PSL. During the past few decades, all possible combinations of these policy interventions can be found in one or more U.S. states. This study estimates the combined associations of these 3 policies with PSL access. The estimates support recent research on the positive effects of PSL mandates, but also indicate that PSL preemption has an offsetting effect. Failure to take account of PSL preemption leads to an over-estimate of the effectiveness of PSL mandates.